Are land values related to ambient air pollution levels? Hedonic evidence from Mexico City. (6th February 2019) - Chakraborti, Lopamudra; Heres, David; Hernandez, Danae
Abstract: This article investigates whether residents of Mexico City value air quality. Our results suggest that air quality improvement in PM10 is equivalent to a marginal willingness to pay (MWTP) of US440.31 per property for the period 2006–2013. The corresponding MWTP for PM2.5 is US880.63, for O3 is US623.78, and for SO2 is as much as US2091.50. These estimates are considerably larger in magnitude compared to the few other studies in similar settings. As a percentage of annual household income, these represent 2.44 per cent for PM10, 4.88 per cent for PM2.5, 3.46 per cent for O3 and 11.59 per cent for SO2 . Our estimates of land value–pollution elasticities for PM10 (−0.26 and − 0.58) are within range of hedonic estimates for total suspended particulate matter in US cities around the 1970s. The corresponding elasticities range from − 0.55 to − 0.84 for PM2.5, from − 0.06 to − 0.49 for O3 and from − 0.11 to − 0.34 for SO2 .